FIBONACCI NUMBERS AND THEIR SIGNIFICANCE IN VARIOUS FIELDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Fibonacci numbers play a significant role in various branches of mathematics. This paper explores the properties of the Fibonacci sequence, methods for investigating them, and their practical applications. Additionally, an algorithmic approach to checking Fibonacci numbers using programming is presented. The study highlights the importance of Fibonacci numbers in natural processes, algorithms, and economics.